Meningkatkan Minat dan Hasil Belajar Matematika melalui Media Audio Visual pada Siswa SDN 13 Tappong - Bachri, Saiful; Tri Bondan Kriswinarso; Lis Sugianto; Sukmawati (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to describe about increasing interest and learning outcomes through the application of visual audiovisual media to mathematical learning. This type of research is This type of research is class action research, The design of this research begins with planning, action, observation and reflection. This research was done at SDN 13 Tappong. The subjects in the study were 26 students consisting of 16 female students and 10 male students. This research instrument consists of an observation sheet on the implementation of learning and a sheet of observation of student activity, elevation of interest in learning, test of learning outcomes and documentation. Based on the results of the study, showed that there was an increase in the learning outcomes and interest of students after learning activities using visual audio media, starting from cycle I and cycle II and has experienced an increase, Cycle I learning outcome of students who achieved the Criteria of Success of 34.62%, student interest in learning reached 62%, and for Cycle II student learning output who reached the criteria of success of students of 92.31% and student learning interest reached 90%. Thus, it can be concluded that the use of visual media audio can improve the interest and learning results of SDN 13 Tappong students